2014
DOI: 10.1093/toxsci/kfu223
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endoplasmic Reticulum Stress in All-Trans-Retinal-Induced Retinal Pigment Epithelium Degeneration

Abstract: Excess accumulation of endogenous all-trans-retinal (atRAL) contributes to degeneration of the retinal pigment epithelium (RPE) and photoreceptor cells, and plays a role in the etiologies of age-related macular degeneration (AMD) and Stargardt's disease. In this study, we reveal that human RPE cells tolerate exposure of up to 5 µM atRAL without deleterious effects, but higher concentrations are detrimental and induce cell apoptosis. atRAL treatment significantly increased production of intracellular reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 43 publications
(68 reference statements)
2
51
0
Order By: Relevance
“…However, in pathologically chronic ER stress, prolonged CHOP expression promotes cell death, and it has been implicated in a number of diseases, including ARMD, neurodegenerative diseases, atherosclerosis, diabetes, and renal disease [27282930]. To investigate the effects of PTX3 knockdown on CHOP expression, we treated control and PTX3 shRNA transfected ARPE-19 cells with tunicamycin (1 µg/mL) and harvested RNA and protein at 6, 12, 24, and 48 hours after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, in pathologically chronic ER stress, prolonged CHOP expression promotes cell death, and it has been implicated in a number of diseases, including ARMD, neurodegenerative diseases, atherosclerosis, diabetes, and renal disease [27282930]. To investigate the effects of PTX3 knockdown on CHOP expression, we treated control and PTX3 shRNA transfected ARPE-19 cells with tunicamycin (1 µg/mL) and harvested RNA and protein at 6, 12, 24, and 48 hours after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…35 In other studies, vitamin A and retinoids were found to exhibit concentration-dependent anti or pro-oxidant effects. [32][33][34][35][70][71][72][73] Thus, it is not universally accepted that all retinaldehydes induce oxidative stress in all conditions. One possible explanation for these disparate findings is that retinaldehydes act in a hermetic fashion as antioxidants in low concentrations and pro-oxidants at higher levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also indicated that A2E and its precursor alltrans retinal could generate ROS inside the RPE cells. [45][46][47] The possible mechanisms were related to the C/EBP homologous protein (CHOP) and GRP18 pathways 32 and cell damage. 48 Moreover, oxidative stress and inflammation are interrelated.…”
Section: Discussionmentioning
confidence: 99%